COVERAGE OF ETHICS ISSUES IN WORKS ON ETIQUETTE - Spanov, Meiirkhan; Tolliboyev, Dilshod (Science technology&Digital finance, 2023)
This article provides information on the statement of morality, norms of morality in artistic-didactic works that are common among the people.